2001
DOI: 10.1128/jb.183.6.1990-1996.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Pseudomonas aeruginosa : Evidence of Iron Override Effects on Quorum Sensing and Biofilm-Specific Gene Regulation

Abstract: Prior studies established that the Pseudomonas aeruginosa oxidative stress response is influenced by iron availability, whereas more recent evidence demonstrated that it was also controlled by quorum sensing (QS) regulatory circuitry. In the present study, sodA (encoding manganese-cofactored superoxide dismutase [Mn-SOD]) and Mn-SOD were used as a reporter gene and endogenous reporter enzyme, respectively, to reexamine control mechanisms that govern the oxidative stress response and to better understand how QS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 51 publications
(52 reference statements)
5
87
1
1
Order By: Relevance
“…However, P. aeruginosa has a particularly high-affinity iron-acquisition system (34), and medium conditioned by pregrowth with this species might have lower levels of iron than media conditioned by other bacteria. Iron is known to be a repressor of a battery of P. aeruginosa genes, including some quorum-controlled genes (35). We observed early production of pyocyanin, a quorumcontrolled pigment involved in iron metabolism (36), when cultures were grown in conditioned medium with acyl-HSL signals.…”
Section: Discussionmentioning
confidence: 86%
“…However, P. aeruginosa has a particularly high-affinity iron-acquisition system (34), and medium conditioned by pregrowth with this species might have lower levels of iron than media conditioned by other bacteria. Iron is known to be a repressor of a battery of P. aeruginosa genes, including some quorum-controlled genes (35). We observed early production of pyocyanin, a quorumcontrolled pigment involved in iron metabolism (36), when cultures were grown in conditioned medium with acyl-HSL signals.…”
Section: Discussionmentioning
confidence: 86%
“…The increase in the number of detectable proteins may be best explained by protein modification, changes in the growth conditions, and/or adaptation to the sessile mode of growth. Environmental factors such as iron, oxygen, and lack of carbon sources have been shown not only to influence protein production within biofilms but also to profoundly impact biofilm formation by P. aeruginosa and other biofilm-forming bacteria (1,11,37,62,69,72).…”
Section: Discussionmentioning
confidence: 99%
“…It is maximally produced under iron-deficient conditions and repressed when Fe 3ϩ is provided in excess (71). Cross-linking of quorum sensing with nutrient availability has been observed for other bacterial systems (8). A preliminary analysis suggested that bradyoxetin-like signal molecules were present in the extracts of various Rhizobium strains as well as other species of the ␣-proteobacterial group (71).…”
Section: Autoinducersmentioning
confidence: 99%